The client satisfaction with device: a Rasch validation of the Arabic version in patients with upper and lower limb amputation - TATAR, YAŞAR (BMC, 2021)
Background The Client Satisfaction with Devices (CSD) module of the Orthotics and Prosthetics Users' Survey is an extensively used questionnaire that measures patients' satisfaction with orthosis and prosthesis. However, the validated version for Arabic speakers (CSD-Ar) is only applicable for orthosis users. Objectives The aim of this study was to evaluate the psychometric proprieties of the CSD-Ar for prosthetics users. Methods The study used a convenience sample of prosthesis users from Saudi Arabia and Turkey (N = 183), who completed the CSD-Ar. The collected data were analysed using Rasch analysis to evaluate item fit, reliability indices, item difficulty, local item dependency, and differential item functioning (DIF) using WINSTEPS version 4.6.1. Results Based on the analysis, the four-response Likert-scale was acceptable, as shown by the category functioning test, All eight items did achieve a fit to the Rasch Model [(infit) and (outfit) mean-square 0.75 to 1.3]. Person separation reliability was 0.76, and item separation reliability was 0.94. A principal component analysis (PCA) showed satisfactory unidimensionality and no local item dependency. The DIF analysis showed no notable dependency among items on participant characteristics in terms of age, gender, duration of use, country, and level of amputation. Conclusion This study contributes to the confidence of using CSD-Ar to evaluate users' satisfaction with different prostheses, affirming the need for further refinement of the quality of the outcome measure.
Keywords: Rasch analysis; Prosthesis; Patient satisfaction; Psychometrics; Rehabilitation; PROSTHETICS USERS SURVEY; SAUDI-ARABIA; ORTHOTICS; VALIDITY; QUESTIONNAIRE; TRAUMA; MODULE